2009
DOI: 10.1007/s10649-009-9196-y
|View full text |Cite
|
Sign up to set email alerts
|

Constructing mathematics in an interactive classroom context

Abstract: This paper investigates the nature of the interaction between the teacher and students as they worked on different mathematics activities in a single classroom over a 10-month period. Sociocultural theories and the Vygotskian zone of proximal development provide the main framework for examining the teaching and learning processes and explaining the incorporation of a four-phase lesson plan as increasing participation of the teacher and students in the teaching and learning process. Drawing on the analyses of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…Learning will be more successful if they are given the opportunity to explain or clarify ideas (Burns, 1990). Lau et al (2009) explains that "the mathematics skills required for youth of today's and adults of tomorrow to function in the workplace are different from that for youth and adults of yesterday". In terms of pedagogy, the development of education now requires teaching strategies that emphasize student involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Learning will be more successful if they are given the opportunity to explain or clarify ideas (Burns, 1990). Lau et al (2009) explains that "the mathematics skills required for youth of today's and adults of tomorrow to function in the workplace are different from that for youth and adults of yesterday". In terms of pedagogy, the development of education now requires teaching strategies that emphasize student involvement.…”
Section: Introductionmentioning
confidence: 99%
“…He suggested that individual and social processes of learning and development are interdependent, and that individuals acquire knowledge through participating in collaborative activities and working with others (Wertsch, 1985;1991;). Vygotsky's proposition provided a framework that has found much resonance in educational research (Tappan, 1998;Mills, 2010;Lau, Singh & Hwa, 2009;Eun, 2010;Rassaei, 2014). His ideas have been further developed in a large number of influential scholarly works that argue for an understanding of learning as socially situated (e.g.…”
Section: Sociocultural Perspective On Learningmentioning
confidence: 99%
“…The environment of small group problem solving provides a natural setting "to supply explanations and elaborate [one's] reasoning" (Kramarski, Mevarech, & Arami, 2002, p. 228); it encourages interpersonal monitoring and reflection (Artzt & Armour-Thomas, 1992); and, it makes students negotiate with each other on viable solutions (Ben-Ari & Kedem-Friedrich, 2000;Lambert, 2002). Past studies have described how the patterns of classroom interactions may facilitate or impede learning (Goos, 2004;Goos & Galbraith, 1996;Goos, Galbraith, & Renshaw, 2002;Lau, Singh, & Hwa, 2009;Truxaw & DeFranco, 2008;Zolkower & Shreyar, 2007).…”
mentioning
confidence: 99%